Σχεδιασμός συστήματος εναέριας μεταφοράς φορτίων από και προς το κτήριο Δωροθέα στον και από τον απέναντι χώρο στάθμευσης - Κωνσταντίνου, Αντρέας (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The thesis which is presented and analyzed in the following pages, was done with the purpose to solve the problem of discomfort caused when freight transport is executed outside the entrance of the Dorothea building. The instructions given for the thesis were clear and focused on an idea in designing a system that allows the user to carry out freight transport in the Dorothea building via an overhead route from the opposite parking area and backwards. This system is based on conveyor chains and through suggesting some ideas which take into consideration many other factors, the necessary calculations were made so as the selection of the remaining parts of the system to be made. The user will place the packets on a cart in the parking area or in the building, upload the cart to the machine, and by a control panel, instruct the system to start the operation to transport the load to the building or to the parking area respectively. In the study, importance was given to the aesthetics and ergonomics of the machine, to safety of course, but also to static, dynamic and economical calculations. Static and dynamic calculations along with all construction drawings were done with Solid Works software.
Keywords: Conveyor chains; Attachments; Cart; Load; Dorothea building; Αλυσίδες μεταφοράς; Προσαρτήματα; Καρότσι; Φορτίο; Κτήριο Δωροθέα